2015
DOI: 10.1007/s10353-015-0318-8
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of airway obstruction caused by wound hematoma after thyroidectomy: an ex vivo study

Abstract: Background Airway obstruction by postoperative hemorrhage after thyroid resection is a serious adverse and potentially life-threatening event. The aim of this study is to investigate if the possible pressure caused by a postoperative hematoma in the neck would be sufficient to compress the trachea and therefore leads to a mechanical airway obstruction.Methods In this ex vivo model varying pressures (0-250 mmHg) were applied on 30 human cadaver tracheas. The primary outcome was the anterior-posterior and latero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…A mean pressure above 227 mmHg is needed to cause a compression of the trachea between 20.8 and 100% [9, 11, 13]. Compartment pressure above 200 mmHg cannot be reached in the lower leg [14] and probably not in the neck.…”
Section: Introductionmentioning
confidence: 99%
“…A mean pressure above 227 mmHg is needed to cause a compression of the trachea between 20.8 and 100% [9, 11, 13]. Compartment pressure above 200 mmHg cannot be reached in the lower leg [14] and probably not in the neck.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the venous drainage must be impaired because of the simultaneously increased pressure in the internal jugular vein. The increased cervical compartment pressure almost reaching the mean arterial blood pressure is not sufficient for a relevant airway compression as reported previously (13). Therefore, a compartment syndrome could explain the mechanism for the decrease in cerebral oxygenation due an increasing cervical compartment pressure.…”
Section: Discussionmentioning
confidence: 63%
“…Harding et al earlier disproved the hypothesis of external airway obstruction and suggested a multifactorial pathogenesis (12). Previously, we could demonstrate in ex-vivo human cadaver tracheas that pressure levels of more than 150 mmHg are required to cause relevant mechanical tracheal obstruction (13). We previously reported on four symptomatic patients with post thyroidectomy hemorrhage and increased cervical compartment pressure between 20 and 40 mmHg at time of revision surgery (14).…”
Section: Introductionmentioning
confidence: 90%
“…The authors of the present issue of European Surgery compose an harmonic symphony of themes and directories reflecting different approaches to the world of surgery and basic science [5][6][7][8][9][10]. In addition, the articles sense the highly positive notion, that there can be short lights of true awareness, off the power-tuned path of the despotism-driven "normal" life within the academy.…”
Section: Dear Readermentioning
confidence: 99%
“…In addition, the articles sense the highly positive notion, that there can be short lights of true awareness, off the power-tuned path of the despotism-driven "normal" life within the academy. The colorful spectrum of papers ranges from molecular to clinical science, from open to laparoscopic and minimally invasive surgery [5][6][7][8][9][10]. The globe of variations indicates that there exist amigos out there in the surgical community who have NOT given up to raise questions, who have NOT given up their wish to discover and to understand and tune themselves with the golden shine (Fig.…”
Section: Dear Readermentioning
confidence: 99%